Asynchronous driving principle and its application to vibration control. - Zhang, Yaohua (Earthquake engineering & structural dynamics.)
The vibration control of megaframes with suspension systems is developed in this paper. The interaction between the megaframe and the suspension systems is first analysed, then asynchronous driving principle is proposed for vibration control of such structures. A numerical example is presented to show the application of asynchronous driving principle in the design of vibration control. The response of the megaframe with suspension systems under evolutionary random excitation indicates the feasibility and effectiveness of the proposed method. The vibration control method, though studied in a special case of the megaframe with suspension systems, is also applicable to the vibration control of combined structures with large secondary to primary mass ratio.